Post-marketing surveillance of doxycycline hyclate capsules used in self-medication in the Maluku I Health Zone, Kinshasa, Democratic Republic of the Congo - MUYA CIDINGI, Bony; NTAMBWE NGOYI, Michel; Bisuta Lifayifi, Beni; Miyila Mundongo, Bernadette; Sita Ngutuka, Glody; Mafuta Kitoko, Devine; Masansa, Victoire; MBINZE KINDENGE, JEREMIE (Orapuh Journal, 2025)
Introduction In the Democratic Republic of Congo, self-medication is a common practice, particularly with antibiotics such as doxycycline hyclate. This raises concerns about safety and efficacy in the absence of medical prescriptions and therapeutic monitoring. Purpose The purpose of this study was to survey pharmacy sellers regarding the most requested antibiotics for self-medication, according to the WHO AWaRe classification, and to evaluate the quality of the most commonly used antibiotic for self-medication in the Maluku I Health Zone. This zone was chosen because it is a border and porous area with potential for smuggling and illicit drug sales, as part of post-marketing surveillance. Methods A descriptive cross-sectional study was conducted among sellers in 101 of 116 pharmacies in a peri-urban area of Kinshasa. The study focused on antibiotics used in self-medication, followed by quality control tests conducted according to the USP–NF 2024 pharmacopoeial standards on 12 different batches of doxycycline hyclate. Results The results showed that 87.06% of vendors participated in the survey, including 84.2% males and 15.8% females, with a mean age of 39.51 ± 9.84 years. Regarding educational level, 47.5% had Bac+0, 40.6% Bac+3, 7.9% Bac+5, and 4.0% other qualifications. In terms of training, 59.4% had studied nursing, while only 2% had studied pharmaceutical sciences. Doxycycline capsules were the most requested antibiotic in the Access category (89.1%), while chloramphenicol capsules were the least used (26.7%). Of the analysed batches, 41.7% had compliant marketing authorisations, 16.7% were unregistered, and 41.7% had non-compliant authorisations. All (100%) batches passed the identification and dissolution tests. However, 25% failed the mass uniformity test, while 58.3% passed the assay test and 41.7% failed. Conclusion Regular post-marketing surveillance is necessary to protect consumers from substandard products, given the high rate of under-dosed medicines found in circulation.